FAKTOR -FAKTOR YANG MEMPENGARUHI PERILAKU SEKS PRANIKAH PADA MAHASISWA AKADEMI KESEHATAN X DI KABUPATEN LEBAK - Sinaga, Eko Sarma Natalia (ARCHIVE OF COMMUNITY HEALTH; Vol 2 No 1 (2013): Juni (2013))
Adolescent sexual behavior is greatly influenced by social environment. Without properselection, adolescent could easily be trapped to adopt unhealthy behaviors. These behaviors willcumulatively accelerate the beginning of sexual activity and could lead to risky sexual behavior.The purpose of this research is to reveal premarital sexual behavior and factors that influence iton Health Academy X students in Kabupaten Lebak. The type of this research is quantitativewith cross sectional approach with 143 samples. Bivariate analysis by chi-square test showed that there was a significant relationship between attitude (p=0.047, ??0.05),  the exposure of pornographic media (p=0.047, ??0.05), and opportunity (p=0.009, ??0.05) to premarital sexualbehavior. It is necessary to improve outreach activities of premarital sexual behavior in campusand out of campus as well as establish and improve information and counseling of premaritalsex in the institution and society.
Keywords: premarital sexual behaviour, the exposure to pornographic media, opportunity.